Improvement the Efficiency of CIGS Thin Film Solar Cells by Changing the Doping of the Absorbent Layer and Adding the InAsP Layer - H. Firoozi; M. Imanieh (Journal of Electrical and Computer Engineering Innovations, 2017)
< p>Background and Objectives: In this article, the functionality of solar cells structure based on CuIn1-xGaxSe2 is investigated. This type of solar cell consists of different layers, namely, ZnO (TCO layer), Cd_S (Buffer layer), CIGS (Absorbent layer), and MO (Substrate layer). Two layers, Cd_S and CIGS, form a PN Junction.  < p>Methods: CIGS thin film solar cell is simulated using SILVACO software. The absorbent layer doping was originally changed.  Later doping was kept constant and P-type layer of InAsP was added. Their effect on cell function was observed and examined. It was observed that after doping some parameters of the solar cell have improved whilst some others have decreased. It was also concluded that examined increase or decrease in the amount of dopant would reduce our efficiencies of solar cell. < p>Results: Added the InAsP layer leads to increased open circuit voltage, short circuit current and the solar cell power, consequently gives the efficiency about 33.2%, which is an acceptable efficiency. < p>Conclusion: It was clear that extreme increase or decrease in the amount of dopant in the absorbent layer can change solar cell parameters, and can improve cell functionality. < p>The amount of dopants can also alter some other solar cell parameters which are not desirable, the added InAsP layer leads to increased open circuit voltage, and short circuit current and the solar cell power, consequently gives the about 33.2%, efficiency which is an acceptable efficiencies.======================================================================================================Copyrights©2018 The author(s). This is an open access article distributed under the terms of the Creative Commons Attribution (CC BY 4.0), which permits unrestricted use, distribution, and reproduction in any medium, as long as the original authors and source are cited. No permission is required from the authors or the publishers.======================================================================================================